The Effect of Exercise Addiction Levels of Physical Education and Sports School and Sports High School Students on Healthy Living Skills - Ramazan Erdogan,; Tugba Mutlu Bozkurt, (Journal of Educational Issues, 2024)
The aim of this study is to examine the effects of exercise addiction levels of physical education and sports school and sports high school students on healthy living skills. The research group consists of 269 (88 female, 181 male) volunteer students studying at Bitlis Eren University School of Physical Education and Sports (124 people) and Bitlis Ziya Eren Sports High School (145 people). In the research, “Personal Information Form” was used as data collection tool, “Exercise Addiction Scale” to determine students’ exercise addiction levels, and “Healthy Living Skills Scale” to determine students’ healthy life levels. The data were analyzed with SPSS 22 statistical package program. Significance level was accepted as p < 0.05. In line with the findings obtained from the research, it was determined that there was a positive and low-level significant relationship between the exercise addiction and healthy living skills scales and the sub-dimensions of the scales. With the gender variable, the total and sub-dimensions of the exercise addiction scale, postponement of individual-social needs and emotional change, tolerance development and passion sub-dimension; the type of school variable and the sub-dimensions of the exercise addiction scale, hyperfocus and emotion change sub-dimension; health priority sub-dimension, which is one of the sub-dimensions of the healthy living skills scale with the height variable; It was determined that there was a statistically significant difference between the exercise frequency variable and the total score of the exercise addiction scale and the sub-dimensions of the scale, extreme focus and emotion change, tolerance development and passion total score (p < 0.05).